Alternatif Pengolahan Limbah Organik Rumah Tangga Untuk Produksi Biogas - Susilowati, Prima Endang (Jurnal Progres Kimia Sains, 2011)
Waste is a source of organic material that can be recycled into biogas. This studysought to produce biogas from the fermentation of organic waste using anaerobic microbesisolated from sewage and cow rumen fluid. The study was conducted in the laboratory-scaleanaerobic reactor with a volume of 750 mL, at room temperature, incubation time of 7, 14, 21,28, 35, 42, 49 days, waste solids concentration 1%, 3%, 5%, 7% and 10 %. CO2 produced wasmeasured by the method of deposition by solution of Ba (OH) 2 is converted into volumeusing the general equation of the ideal gas. The difference between the total gas volumeproduced by CO2 gas is methane gas volume value (CH4). The results showed the highestproduction of waste solids obtained at 7% concentration, incubation time of 42 days. Biogas isproduced 99.86 mL / g litter, the total amount of biogas produced during the 7 weeks of 537mL / gram of waste.